Morbidity and mortality profile of neonates: a five-year retrospective study in a tertiary care neonatal unit in Kolkata - Sasmal, Suvashri; Habibullah, S. K. Md; Shetty, Asha P.; Saha, Bijan; Mukherjee, Suchandra (International Journal of Contemporary Pediatrics, 2024)
Background: Neonatal mortality and morbidity pattern reflects a nation’s efficiency and effectiveness of health care services. There is a paucity of reliable data in India on this, while India Newborn Action Plan (INAP) targets single digit neonatal mortality by 2030. Aim was to identify the morbidity and mortality profile of neonates admitted to a tertiary neonatal care unit. Methods: This retrospective descriptive study was conducted at a tertiary care neonatal unit in Kolkata. Data of neonates admitted in this unit were extracted from admission, discharge, and death registers, compiled, and analyzed from January 2015 to December 2019. Neonates brought dead to the unit were excluded. Results: A total of 10301 neonates were admitted during the study period of which 75.05% were inborn. Most of them were male (55.46%) and only 0.70% had differential sexual disorders. A total of 709 deaths were recorded during the study period equating to a rate of 6.9 deaths per 100 neonatal admissions. The major cause of admission was neonatal hyperbilirubinemia (19.30%) followed by congenital anomalies (11.15%), respiratory distress syndrome (10.58%), prematurity (9.72%), and birth weight <1800 grams. (9.51%), perinatal asphyxia (8.11%) and maternal sickness (8.09%). Among congenital anomalies, anomalies related to the gastrointestinal system were most frequent (30.81%). Congenital anomalies (29.9%) were the leading cause of neonatal mortality followed by perinatal asphyxia (17.07%). Conclusions: The commonest causes of neonatal morbidity and mortality were congenital anomalies. Thus, special focus has to be given to the management of congenital malformation in tertiary care units.